Relationships between type and duration of training and well-being status of volleyball athletes - Ricardo Franco Lima; Ana Filipa Silva; José Afonso; Rui Silva; Henrique de Oliveira Castro; Filipe Manuel Clemente (Revista Brasileira de Cineantropometria e Desempenho Humano, 2023)
The purpose of this study was to describe weekly variations in the type and duration of training, as well as wellness-related parameters, in elite volleyball players. Twenty-four youth elite volleyball players from the French national team (age: 17.8 ± 1.0 y.o.) were monitored daily, and the type of training, training duration, participation in matches, and wellness status were measured over 22 weeks. Volleyball training duration varied from 100 to 510 minutes per week, while strength and conditioning training duration varied from 97 to 262 minutes per week. Fatigue levels varied from 1.5 to 2.8 A.U., and delayed onset muscle soreness (DOMS) varied from 1.5 to 2.5 A.U. Large positive correlation were found between sleep and match duration (r = 0.64) and between stress and weekly volume (r = 0.52). Additionally, moderate positive correlation were found between fatigue and match duration (r = 0.36); between sleep and weekly volume (r = 0.35); between DOMS and match duration (r = 0.43); between stress and strength training (r = 0.42), volleyball training (r = 0.35), and match duration (r = 0.47). The present study revealed natural variations in training volume across the season and moderate dependency between weekly training/match durations and wellness status.